Medilink - Raghad Ayman Yameen; Yumna Eyad Abu Hanish (Dr. Samer Arandi, 2026)
This graduation project presents the development of MediLink, an integrated healthcare platform designed to connect patients, doctors, and administrators through a modern mobile application supported by artificial intelligence capabilities. The system consists of three main components: a Flutter-based mobile application that provides a user-friendly interface supporting multiple platforms (Android, iOS, and Web), a backend server built with Node.js and Express to manage business logic and data processing, and an AI microservice that utilizes Google Gemini API to provide intelligent features such as symptom checking and medical report analysis. The platform supports three user roles: patients who can book appointments, manage medications, upload medical reports, and consult doctors via paid chat; doctors who can manage their schedules, write prescriptions, view patient medical histories, and set consultation fees; and administrators who oversee user management, approve doctor registrations, manage medical specialties, and monitor system analytics. Key features include JWT-based authentication, real-time push notifications via Firebase Cloud Messaging, automated reminders for appointments and medications, secure file storage, and responsive design that adapts to different screen sizes. The backend utilizes PostgreSQL with JSONB data type for flexible reminder tracking, and the frontend employs Riverpod for state management and GoRouter for navigation. The project was developed as a graduation requirement for the Bachelor's degree in Computer Engineering at An-Najah National University. While MediLink demonstrates the potential of integrating modern technologies in healthcare, it remains an academic prototype and is not intended for real medical use. The AI features are experimental and should not replace professional medical advice.
--
The primary objectives of this graduation project are to develop a cross-platform mobile application using Flutter that runs on Android, iOS, and Web platforms, providing a seamless experience for patients, doctors, and administrators. The project also aims to create a robust backend server using Node.js and Express to handle authentication, business logic, data persistence, and API services. Another key objective is to integrate artificial intelligence capabilities using Google Gemini API to provide intelligent features such as symptom checking and medical report analysis, enhancing the platform's diagnostic support. The project further aims to implement role-based access control supporting three distinct user roles including Patient, Doctor, and Admin, each with customized dashboards and permissions. Additionally, the project seeks to enable real-time notifications utilizing Firebase Cloud Messaging (FCM) to send automated reminders for upcoming appointments and medication schedules, improving patient adherence. The project also aims to provide secure data management ensuring encrypted storage of medical records, prescriptions, and personal information using JWT-based authentication. A responsive user interface that adapts to different screen sizes including mobile, tablet, and desktop is another important objective. Finally, the project aims to document the system comprehensively including system architecture, API endpoints, database schema, user manuals, and testing procedures for future reference and maintenance.
--
Keywords: Industry